ChemInform Abstract: N‐Pyrrolidine‐Based α/β‐Peptides Incorporating ABOC, a Constrained Bicyclic β‐Amino Acid, for Asymmetric Aldol Reaction Catalysis. Issue 28 (June 2016) - Milbeo, Pierre; Maurent, Kelly; Moulat, Laure; Lebrun, Aurelien; Didierjean, Claude; Aubert, Emmanuel; Martinez, Jean; Calmes, Monique
Abstract: Catalytic properties of 15 N‐pyrrolidine‐based α, β‐peptides incorporating a constrained 2‐aminobicyclo[2.2.2]octane carboxylic acid (ABOC) are evaluated in the asymmetric aldol reaction from acetone and some p‐substituted benzaldehydes.